Mental health issues and sleep quality of Indian employees and higher education students during COVID-19 lockdown. (30th July 2021) - Radhakrishnan, B.L.; Kirubakaran, E.; Belfin, R.V.; Selvam, Sudhakar; Sagayam, K. Martin; Elngar, Ahmed A.
India implemented a prolonged lockdown to contain the spread of COVID-19. Our study aimed to assess the mental health difficulties and influence of lockdown stressors among Indian higher education students' and employees of the government, private sector during the COVID-19 lockdown. We collected the basic demographic, sleep generalised anxiety disorder (GAD), perceived stress scale (PSS) and sleep quality data from 676 participants using a web-based cross-sectional survey. Among the participants, the overall prevalence of GAD and PSS were 22.9%, 15.7% (low), 79.4% (medium), 4.7 (high), respectively. Younger participants reported higher GAD and PSS symptoms. Lockdown stressors have a significant correlation with GAD and PSS. In addition, the increased mobile phone usage significantly affects sleep latency, and sleep quality (p < 0.001) is a subject of concern. As part of global preparedness measures, continuous monitoring of sleep and the psychological impacts of outbreaks should become standard practice.